Discovery of DNA Aptamers Targeting SARS-CoV-2 Proteins and Protein Binding Epitopes Identification for Label-Free COVID-19 Diagnostics - Poolsup, Suttinee (Université d'Ottawa / University of Ottawa, 2023)
The spread of COVID-19 has affected billions of people across the globe with the challenges of less accurate and time-consuming detection approaches. Especially, new variants with various mutations in the spike protein can escape immune responses as well as a low viral load in clinical samples can trigger a false-negative test result. Due to high immunogenicity and abundant expression during viral infection, SARS-CoV-2 nucleocapsid (N) protein could be an alternative diagnostic marker, together with targeting the S1 subunit of SARS-CoV-2 spike protein. This study aimed to develop a label-free optical aptasensor fabricated with novel ssDNA aptamers to detect the N and S1 proteins. The aptamers selected using asymmetric emulsion PCR-SELEX and their binding affinity and cross-reactivity were characterized by using bio-layer interferometry. The tNSP3 aptamer (44 nt) was identified to bind the N protein of wild type and Delta and Omicron variants with high affinity (KD in the range of 0.6 – 3.5 nM). Furthermore, the aptamers targeting the S1 subunit were also discovered in order to expand an additional tool for aptamer-based biosensors used in COVID-19 detection. The S1-tSP10 aptamer with 40 nt performed better affinity than other S1-targeting aptamers, and this aptamer possessed the KD about 15 nM binding to the S1 protein of wild type and Omicron variant. Utilizing tNSP3 and S1-tSP10 aptamers to separately detect the N and S1 proteins spiked in human saliva evinced the potential of these aptamers in the function of aptamer-based BLI with LODs of 4.5 nM and 19 nM corresponding to tNSP3 and S1-tSP10 aptamers, respectively. To get insight into where the aptamers bind to their target proteins, mass spectrometry analysis was performed along with the molecular dynamic simulation. The identified epitope peptides are localized within the RNA-binding domain and CTD of the N protein as well as RBD of the S1 protein. Hence, we confirmed the performance of the aptamers as a label-free analytical tool for COVID-19 diagnosis, and also knowing the binding epitopes can be essential for improving biomedical applications in therapeutics.
Keywords: Label-free optical aptasensor; COVID-19 diagnosis; Bio-layer interferometry; Aptamer selection; SARS-CoV-2 nucleocapsid and S1 subunit proteins; Binding motif identification